Gender underlies the formation of STEM research groups. Issue 9 (1st April 2020) - Start, Denon; McCauley, Shannon
Abstract: Research groups are the cornerstone of scientific research, yet little is known about how these groups are formed and how their organization is influenced by the gender of the research group leader. This represents an important gap in our understanding of the processes shaping gender structure within universities and the academic fields they represent. Here, we report the results of an email survey sent to department chairs and discipline‐specific listservs. We received responses from 275 female and 175 male research group leaders. Most respondents were biologists ( n = 328) but psychology ( n = 27), chemistry ( n = 16), physics ( n = 32), and mathematics ( n = 30) were also relatively well represented. We found that men were self‐reported as overrepresented in research groups in the physical sciences, particularly at later career stages. Within biology, male and female group leaders reported supervising a disproportionate number of same‐gender trainees (students and postdoctoral fellows), particularly early in their careers. These self‐reported patterns were driven primarily by gender‐based differences in the pool of students applying to their research groups, while gender differences in acceptance rates played a seemingly smaller role. We discuss the implications of our results for women continuing into the professoriate and for the recruitment of young scientists into research groups. Abstract : Gender differences are pervasive in STEM, yet we know relatively little about the factors structuring gender differences in research groups—the fundamental unit of scientific investigation. We show that gender of the applicant pool and the principal investigator interact to shape gender representation in research groups. Our study has important implications for the continuation of women in STEM fields and for the performance of science as a whole.